The ‘Song of Release’ Twenty-nine Years after its Discovery - Martino, Stefano de (Altorientalische Forschungen, 2012)
This papers deals with the important Hurrian literary composition ‘the Song of Release’. Its first tablet KBo 32.11 is discussed and a new interpretation of lines iv 13´–14´ is proposed. Further, the tradition of these texts and that of the so-called ‘Parables’ often associated with them is examined.